Actualization of the South Podlasie Dialect Elements in the Artistic Works by Stepan Sydoruk (Linguostylistic Studies, 2018)
The issue of literary and dialectal languages interaction is a topical problem of theoretical and practical importance in modern linguistics. One of its aspects is the use of dialects in the artistic texts that influence the dynamics of style and general literary norms through the aesthetic function of the language. The elucidation of the individual author's specifics of presenting the communicative elements in the artistic texts contributes to creating a complete picture of the tendencies in dialectal-literary interaction in general and the modern trends in the development of language and literature in particular.The interest of the writers of Podlasie (Republic of Poland) to the folk language clearly manifested itself in the 80s of the twentieth century. The young poets, the bearers of the Ukrainian dialects, having realized their distinctiveness from the Poles and Bielorussians, began to seek self-expression in the artistic word, actualizing the features of the local speech in their texts. Stepan Sydoruk supported the trend of creating literary works in Ukrainian using dialectal elements. The source of the research  are the poetic and prose texts from the collection of Stepan Sydoruk «All the Cranes are Assembling». The purpose of the study is to trace multilevel features of the South Podlasie Ukrainian dialect in the works of Stepan Sydoruk.The analyzed texts convincingly testified that S. Sydoruk, writing his works predominantly in the Ukrainian literary language, reproduces various levels of the Podlasie dialect peculiarities with varying degrees of frequency and sequence. At the phonetic level, he is disposed to preserve the specificity of reflexion of the ancient and positional variants of modern vowel phonemes, differences in consonant phonemes loading, combinatorial sound changes. At the morphological level, the most prominent dialect phenomena are those connected with the peculiarities of the substitution of the nominal parts of language and verbs. The features of the morphemic composition of adverbs are also in the focus of the study. S. Sydoruk also used a lot of dialectal tokens, but unfortunately, did not explain their meaning, which complicates the perception of the texts by an unprepared reader.The study seeks to reveal the most accurate reproduction of all the features of the dialect and argues that it is hardly possible at all. However, the use of the Podlyasie dialect elements is undoubtedly the stylistic device that allows to reproduce the language specifics of the region and, moreover, they create an effect of a subjective narrative.
Keywords: Stepan Sydoruk; Pidliashshya; dialect; Podlasie dialect; dialectisms